A framework for assessing the contribution of UK local authorities toward compliance with the EU ambient air quality directive. Issue 2 (28th January 2022) - Fremantle, Katherine; De Vito, Laura; Williams, Ben; Longhurst, James
Abstract : Implementation outcomes of the Ambient Air Quality Directive (AAQD) (2008/50/EC)) are weak across European Union (EU) member states. In the UK, Local Authorities (LAs) must work toward reducing air pollution, however, means of assessing the extent and effectiveness of their contribution are limited. This paper develops a framework to evaluate policies implemented by UK LAs to address air pollution and applies it to Air Quality Action Plans (AQAP) of five cities. It looks at how, and the extent to which, LA air quality policies align with AAQD requirements, thus advancing empirical and academic knowledge on implementation literature surrounding multi-level governance, specifically the policy disconnect between the AAQD and UK Local Air Quality Management (LAQM). The application of the framework shows how LAs can better integrate AQAPs into their LAQM plans to assess, develop, improve and implement their air quality policies on the ground.